The Sublime, Nature and Catholicism. The Italian Journey as Goethe's Aesthetical Repertoire - Wilma Patrícia M. D. Maas (Pandaemonium Germanicum: Revista de Estudos Germanísticos, 2017)
Goethe’s Journey to Italy is here understood less as an autobiography than as an encyclopedic work of art. Here we can see many different speeches and goals reunited under common suggestions and themes, without a clear articulating line. This article intends to identify Goethe’s reception of natural and artistic forms during his stay in Italy as a possible guideline for this work